TREATMENT OF A HUGE ODONTOGENIC FIBROMA WITH ANTERIOR ILIAC CREST AND IMPLANT SUPPORTED FIXED PROSTHESIS: A CASE REPORT - Emrah Soylu; Erdem Kılıç; Mustafa Zortuk; Alper Alkan (Cumhuriyet University, 2017)
Purpose: Odontogenic fibroma (OF) is a rare benign odontogenic neoplasm and classified as central (COF) and peripheral (POF) type and COF has two sub groups; epithelium-poor (simple) type and epithelium-rich (WHO or complex) type. Treatment modality of OF is surgical excision. However, after large-scaled excision, reconstruction of the defect may be required. Case Report: 39 year old male patient referred with complain of a painless swelling in anterior maxilla. Incisional biopsy showed that the lesion is simple type OF. Under general anesthesia, lesion enucleated and defect reconstructed with anterior iliac graft. After 8 months, 3 dental implants were placed and final reconstruction was done with implant supported fixed prosthesis. Dıscussıon: OF is a benign and very rare odontogenic neoplasm accounting for 0-5.5% of odontogenic tumors. Treatment modality of OF is enucleation and curettage, but after enucleation of huge OF, reconstruction may be challenging by the size of the defect. Anterior iliac graft is a gold standard among all autologous bone graft sources and it also provides adequate bone for the reconstruction of the maxillofacial defects, otherwise it is possible to place implants with acceptable resorption rates. Conclusion: Reconstruction of the jaw defects with anterior iliac graft and implant supported fixed prosthesis after enucleation of huge size tumors such as COF, is a feasible method